Sodium channel slow inactivation interferes with open channel block - Hampl, Martin (Sci Rep, 2016)
Mutations in the voltage-gated sodium channel Nav1.7 are linked to inherited pain syndromes such as erythromelalgia (IEM) and paroxysmal extreme pain disorder (PEPD). PEPD mutations impair Nav1.7 fast inactivation and increase persistent currents. PEPD mutations also increase resurgent currents, which involve the voltage-dependent release of an open channel blocker. In contrast, IEM mutations, whenever tested, leave resurgent currents unchanged. Accordingly, the IEM deletion mutation L955 (ΔL955) fails to produce resurgent currents despite enhanced persistent currents, which have hitherto been considered a prerequisite for resurgent currents. Additionally, ΔL955 exhibits a prominent enhancement of slow inactivation (SI). We introduced mutations into Nav1.7 and Nav1.6 that either enhance or impair SI in order to investigate their effects on resurgent currents. Our results show that enhanced SI is accompanied by impaired resurgent currents, which suggests that SI may interfere with open-channel block.